Public Health and the Epidemic of Incarceration - Dumont, Dora M. (2012)
An unprecedented number of Americans have been incarcerated in the past generation. In addition, arrests are concentrated in low-income, predominantly nonwhite communities where people are more likely to be medically underserved. As a result, rates of physical and mental illnesses are far higher among prison and jail inmates than among the general public. We review the health profiles of the incarcerated; health care in correctional facilities; and incarceration’s repercussions for public health in the communities to which inmates return upon release. The review concludes with recommendations that public health and medical practitioners capitalize on the public health opportunities provided by correctional settings to reach medically underserved communities, while simultaneously advocating for fundamental system change to reduce unnecessary incarceration.